River-basin planning and management: the social life of a concept - Molle, Francois (Elsevier, 2009)
The concept of a river basin as a management or planning unit has gone through several stages and is in a state of flux. From its western ''discovery? in the 18th century to its advent as the overriding concept behind European water policy, the river basin has been conjured up and mobilized in evolving contexts with varying intentions. Associated with utopian ideas of the late 19th century, it supported ideas of full control of the hydrologic regime and multipurpose dam construction in the 1930-1960 period, then partly faded and was revived to address water-quality problems, before reemerging in the 1990s as the cornerstone of Integrated Water Resources Management (IWRM), enriched and blended with watershed- and ecosystem-management approaches. This article recounts the evolution of the concept of a river basin and how it has been associated with various strands of thinking and sometimes co-opted or mobilized by particular social groups or organizations to strengthen the legitimacy of their agendas. Beyond its relevance as a geographical unit for water resources development and management purposes, the river basin is also a political and ideological construct, with its discursive representations and justifications, closely linked with shifting scalar configurations, both ecological and in terms of regulatory regime or governance. How interconnected and nested waterscapes can be managed by discontinuous nested political/administrative and social levels remains a fundamental question fuelling an endless search for elusive governance systems that would unite nature and society.